Characterising the effect of antimalarial drugs on the maturation and clearance of murine blood-stage Plasmodium parasites in vivo. Issue 14 (December 2017) - Khoury, David S.; Cromer, Deborah; Elliott, Trish; Soon, Megan S.F.; Thomas, Bryce S.; James, Kylie R.; Best, Shannon E.; Aogo, Rosemary A.; Engel, Jessica A.; Gartlan, Kate H.; Akter, Jasmin; Sebina, Ismail; et al.
Graphical abstract: Highlights: Artesunate rapidly inhibits Plasmodium development in vivo. Artesunate-affected parasites are removed with a 6.7 h half-life in mice. Removal is largely mediated by phagocytes, especially removal of ring-stage parasites. Mefloquine (MQ) is unable to fully inhibit parasites in vivo within 6 h of treatment. MQ-affected parasites are removed 30% slower than artesunate-affected parasites. Abstract: The artemisinins are the first-line therapy for severe and uncomplicated malaria, since they cause rapid declines in parasitemia after treatment. Despite this, in vivo mechanisms underlying this rapid decline remain poorly characterised. The overall decline in parasitemia is the net effect of drug inhibition of parasites and host clearance, which competes against any ongoing parasite proliferation. Separating these mechanisms in vivo was not possible through measurements of total parasitemia alone. Therefore, we employed an adoptive transfer approach in which C57BL/6J mice were transfused with Plasmodium berghei ANKA strain-infected, fluorescent red blood cells, and subsequently drug-treated. This approach allowed us to distinguish between the initial drug-treated generation of parasites (Gen0 ), and their progeny (Gen1 ). Artesunate efficiently impaired maturation of Gen0 parasites, such that a sufficiently high dose completely arrested maturation after 6 h of in vivo exposure. In addition, artesunate-affected parasites were cleared from circulation with a half-life of 6.7 h. In vivo cell depletion studies using clodronate liposomes revealed an important role for host phagocytes in the removal of artesunate-affected parasites, particularly ring and trophozoite stages. Finally, we found that a second antimalarial drug, mefloquine, was less effective than artesunate at suppressing parasite maturation and driving host-mediated parasite clearance. Thus, we propose that in vivo artesunate treatment causes rapid decline in parasitemia by arresting parasite maturation and encouraging phagocyte-mediated clearance of parasitised RBCs.